Sexual Risk Behaviors Among Men Who Have Sex with Men (MSM) Using Pre-Exposure Prophylaxis (PrEP): A Systematic Review (Caring: Indonesian Journal of Nursing Science, 2025)
According to 2023 global estimates, approximately 39.9 million individuals were living with HIV (Human Immunodeficiency Virus), with 1.3 million new infections reported. Men who have sex with men (MSM) continue to represent a key population at heightened risk. When used consistently, pre-exposure prophylaxis (PrEP) has been shown to reduce the risk of HIV transmission by more than 90%. Stigma, limited awareness, and concerns about reduced condom use hinder its effectiveness. This review examines whether PrEP increases or decreases sexual risk behaviors, such as unprotected anal intercourse, among MSM to inform better HIV prevention strategies. Search in PubMed and ScienceDirect identified 585 records, with 26 studies meeting the inclusion criteria after screening and quality assessment using the CASP checklist. Out of these, 14 high-quality articles, including cohort, cross-sectional, and randomized controlled trials, were analyzed. Studies focused on MSM aged 15 and older using PrEP, excluding non-MSM populations, qualitative reports, and reviews. Two reviewers independently screened and extracted the data, resolving the discrepancies through discussion. A narrative synthesis examined patterns of sexual risk behavior and PrEP impact. Subsequently, PrEP significantly reduces HIV transmission but is linked to risk compensation behaviors, such as decreased condom use and increased high-risk sexual activities. Social and cultural factors, including stigma and familism, influence adherence to safe practices. Comprehensive interventions integrating PrEP with education, Sexually Transmitted Infection (STI) screening, and psychosocial support are essential. Governments and health providers should prioritize expanding PrEP access, improving adherence support, and integrating condom promotion to achieve greater HIV prevention impact on MSM communities.